Delayed Positive Effects of an Acute Bout of Coordinative Exercise on Children's Attention. Issue 2 (October 2015) - Schmidt, Mirko; Egger, Fabienne; Conzelmann, Achim
Since attention is an important prerequisite for learning, it is particularly worthwhile to promote it in schools, through specific interventions. The present study examined the effects of an acute bout of coordinative exercise in physical education on the attention of primary school children. A total of 90 fifth grade primary school children (41 boys, 49 girls; M = 11.0 yr., SD = 0.6) participated in the study and were randomly assigned to either the experimental or the control group. The experimental group received a cognitively demanding physical education lesson consisting of different coordinative exercises; the control group attended a normal sedentary school lesson. Before, immediately after, and 90 min. after each experimental condition, the children's attentional performance was tested using the revised version of the d2 Test of Attention (d2–R). Results of the repeated-measures analysis of variance (ANOVA) revealed that children's attentional performance increased through the specifically designed physical education lesson, not immediately but 90 min. after cessation. The results are discussed in terms of mechanisms explaining the relationship between acute physical exercise, and immediate and delayed effects on attention.